Country-specific determinants of intra-industry trade in Portugal - Faustino, Horácio C. (2010)
Based on the theoretical models of Helpman and Krugman (1985), Falvey and Kierzkowski (1987) and Flam and Helpman (1987) and on the empirical studies of Greenaway, Hine and Milner (1994) and Hummels and Levinsohn (1995), we use a static and dynamic panel data approach to test the country-specific determinants of Portuguese intra-industry trade (IIT). We include income variables together with supply-side variables in order to test the demand similarity and factor endowments difference hypotheses. The results suggest that the Linder hypothesis is confirmed and that differences in income levels have a positive (negative) effect on vertical IIT (horizontal IIT and IIT). However, our findings only partially confirm Helpman and Krugman's theoretical predictions.